Discovery of a new subfamily expands the catalytic versatility of vanillyl alcohol oxidases - Weindorf, Nils; Rapsch, Tobias; van Berkel, Willem J. H.; Tischler, Dirk (Frontiers in Microbiology, 2026)
Flavoenzymes of the 4-phenol oxidoreductase family are versatile biocatalysts that catalyze the oxidation of a wide variety of phenol derivatives to alcohols, aldehydes, ketones or alkenes. The promiscuous FAD-dependent vanillyl alcohol oxidases from Penicillium simplicissimum (PsVAO) and Diplodia corticola (DcVAO) have been described to catalyze the oxidative deamination of p-hydroxybenzylamines, giving rise to valuable flavor compounds, but starting from p-alkyl substituted phenols, the ketones are usually not accessible as these oxidases preferably stop at chiral benzylic alcohols. Here we took a closer look into the fungal VAO family with the aim to identify new members that can perform this deamination reaction and also the overoxidation of benzylic alcohols to ketones at a sufficient rate for application. Phylogenetic and amino acid cluster analysis revealed one clade that differed significantly in the constitution of the active site, while maintaining residues essential for catalysis. From this clade, five candidates were chosen for investigation, which revealed that VAO from Paecilomyces variotii (PvVAO) showed promising activities with vanillylamine and 4-(1-amino)ethylphenol, especially above pH 9.0, while also offering the ability to perform the overoxidation of p-alkyl substituted phenols toward ketones. Hence, the identified PvVAO offers two reaction routes toward benzylic ketones.